Diverse Interpretations of the Sino-Indian Conflict - Riaz A. Khokhar (CISS Insight Journal, 2022)
In the summer of 2020, China mobilized its military forces along its undefined border with India in the mountainous Galwan valley. Analysts have made different interpretations of China’s move. One school of thought considers China’s military mobilization as part of an aggressive campaign against neighbors. Another school regards China’s actions as defensive and responsive to India’s pugnacious rhetoric and military campaign. Yet another line of thinking views China’s military response as much required to check India’s territorial expansionism and military aggression in its neighborhood. Each of these perspectives has a logical base. This paper will examine all of these viewpoints, and in doing so, will also seek to explore if an interpretation of the Sino-Indian conflict, where Beijing’s reaction is construed as aggression, can be a catalyst in a three-tier process of undermining security in South Asia. One, the incident buttressed the perception about India as a potential counterweight to China; second, India’s enhanced importance will drive the western powers to arm India with advanced military technologies; and third, in the process, they disregard India’s domestic human rights violations and democratic backsliding as well as regional military aggression.